Life history and genetic characterisation of sea trout Salmo trutta in the Adriatic Sea. (11th December 2019) - Splendiani, Andrea; Fioravanti, Tatiana; Ruggeri, Paolo; Giovannotti, Massimo; Carosi, Antonella; Marconi, Mario; Lorenzoni, Massimo; Righi, Tommaso; Nisi Cerioni, Paola; Caputo Barucchi, Vincenzo
Abstract: The brown trout Salmo trutta is characterised by both anadromous (sea trout) and resident populations, naturally occurring in Atlantic and Ponto‐Caspian rivers. Sea trout are currently considered absent from rivers of the Mediterranean area, probably because of the non‐optimal chemical–physical characteristics of the Mediterranean Sea. However, the occasional bycatch of smoltified S. trutta in the Adriatic Sea is well known among fishermen and the biological explanation of this phenomenon is still controversial. The aim of this study was to compare the genetic diversity of freshwater and marine brown trout to try to understand the factors underlying the presence of putative anadromous brown trout in the Adriatic Sea. In this study, we analysed the genetic diversity of: (1) wild brown trout collected from the Esino River (central Italy); (2) a domestic strain of brown trout used for stocking the study area; and (3) a sample of Adriatic sea trout collected near the outlet of the Esino River. Together with genetic analysis, we carried out scale analysis in order to track the freshwater/marine stages of the life cycle in the sea trout samples. The genetic characterisation was carried out by polymerase chain reaction–restriction fragment length polymorphism analysis of the mtDNA fragment ND‐5/6 and the nuclear locus LDH‐C1* and by genotyping 15 microsatellite loci. The genetic polymorphism obtained was used to investigate intra‐ and inter‐population genetic diversity, rates of genetic introgression between wild and domestic samples and the origin of sea trout specimens by using assignment tests. Our genetic analyses demonstrated that the sea trout analysed in this study are from the domestic strain of Atlantic origin used in central Italy for stocking activities. The level of genetic introgression between native and domestic samples is high in the Esino River. The populations more resilient to introgressive hybridisation appeared to be those living in the portion of the river network dominated by carbonate rocks. Assignment tests (GeneClass) suggest the existence of a link between stocking efforts and the freshwater origin of the sea trout. In addition, data obtained from the analysis of scales, size measurement, and sex determination showed a pattern of smolt age, size, and sex ratio very similar to those observed in other anadromous populations. In conclusion, the present study highlighted that sea trout from the central Adriatic Sea originated from brown trout of Atlantic origin inhabiting the Esino River. Their seaward migratory behaviour could represent a consequence of an active migration instead of a passive displacement by water flow. Our results also showed that traditional stocking practices represent a negative activity for the conservation of the last Mediterranean native S. trutta populations.